“Identificación de los patógenos y dano económico de la muerte de plantulas de cualantro (coriandrum sativum) en Lamas” - García Saavedra, Jhon (2003)
The work present investigation was carried out during the months of June to September of 1996, With the objective of identifying the pathogenic and economic damage of the main illnesses that caused the marchitez and death of plants in cylantro (Coriandrum sativum), in horticultura! fields of the Sector Quilloallpa, district and county of you Lick. The studied treatments were: 1 am Accustomed to without disinfecting or witness (SSD); Seed without disinfecting (SesD); 1 am Accustomed to disinfected with formol to 2% (SDF); Seed disinfected with Thiram to the 3 o/oo (DST); Seed disinfected with Tolclofos (SeDTO); Pulverizations with copper chloride to the 4 oloo (PO); which were subjected to a design of complete blocks at random. The isolated and identified mushrooms were: Fusarium spp; Rhizoctonia sp; Pythium sp; Colletotrichum sp; it would Altemate sp. In the patogenicidad test it was positiva the species of the gender Fusarium and the incidence of the illness marchitez and death at the field level were bigger in the treatment 3 (98.58%) comparatively with the treatment 2 (92.65%) that obtained a smaller incidence. This treatment gave bigger yield of 2 416.67 Kg/ha, leaving a net utility of 24.70%.